Full scope simulation of VVER-1000 blowdown source and containment pressurization in a LBLOCA by parallel coupling of TRACE and CONTAIN. (October 2021) - Safarzadeh, Omid; Noori-kalkhoran, Omid; Gei, Massimiliano; Morini, Lorenzo; Ahangari, Rohollah
Abstract: Nuclear power plants containment plays an important role as last-defined barrier in defense in depth approach against the release of radioactive material to the environment. In this study, a parallel processing couple has been developed to full scope analysis of blowdown source and containment pressurization parameters in a LBLOCA accident. To achieve this goal, primary and secondary loops of a VVER-1000/V446 were first simulated in TRACE V5.0 and steady-state results have been validated against reference data. The second step deals with containment simulation in CONTAIN 2.0 with new modified 30-cells models. A parallel processing interface was developed in MATLAB to couple TRACE and CONTAIN in the break point. Containment average pressure has been fed back to TRACE as forcing function of blowdown source in each time step during pressurization phase (coupling point). Finally, results of blowdown and containment pressurization have been validated against final safety analysis report (FSAR). Results of simulation confirm that the maximum containment pressure can reach 0.36 MPa and 0.395 MPa for this study and FSAR respectively that are lower than the maximum design absolute pressure of 0.46 MPa, so containment maintains its integrity during this accident. Temperature profiles of different control volumes inside containment during accident follow the FSAR profiles in terms of shape and value that show the ability of developed parallel coupling to full scope simulation of accidents accurately. Highlights: Parallel processing couple of Blowdown source and containment pressurization. Modified TRACE and CONTAIN models for primary loop and containment simulations. Considering the mutual effects of Blowdown source and containment pressurization. Validation of containment pressurization during LBLOCA by developed couple. Demonstrating the effects of spray on containment pressurization.